2019
DOI: 10.1002/open.201900116
|View full text |Cite
|
Sign up to set email alerts
|

Insights into Allosteric Control of Human Blood Group A and B Glycosyltransferases from Dynamic NMR

Abstract: Human blood group A and B glycosyltransferases (GTA, GTB) are retaining glycosyltransferases, requiring a catalytic mechanism that conserves the anomeric configuration of the hexopyranose moiety of the donor substrate (UDP‐GalNAc, UDP‐Gal). Previous studies have shown that GTA and GTB cycle through structurally distinct states during catalysis. Here, we link binding and release of substrates, substrate‐analogs, and products to transitions between open, semi‐closed, and closed states of the enzymes. Methyl TROS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Significant differences in the thermodynamic contributions to the binding of the natural donor compared to that of synthetic analogs have also been confirmed . Recent studies utilizing dynamic NMR performed by Flügge and Peters show, surprisingly, a mutual allosteric cooperativity among the donor and the acceptor substrates, wherein the association and dissociation rates of each regulate those of the other via conformational changes in the enzyme, altogether enhancing the binding affinity of both the substrates to drive the completion of catalysis …”
Section: Cooperativity and Thermodynamics Of The Substrate Bindingmentioning
confidence: 88%
See 1 more Smart Citation
“…Significant differences in the thermodynamic contributions to the binding of the natural donor compared to that of synthetic analogs have also been confirmed . Recent studies utilizing dynamic NMR performed by Flügge and Peters show, surprisingly, a mutual allosteric cooperativity among the donor and the acceptor substrates, wherein the association and dissociation rates of each regulate those of the other via conformational changes in the enzyme, altogether enhancing the binding affinity of both the substrates to drive the completion of catalysis …”
Section: Cooperativity and Thermodynamics Of The Substrate Bindingmentioning
confidence: 88%
“…13 Recent studies utilizing dynamic NMR performed by Flugge and Peters show, surprisingly, a mutual allosteric cooperativity among the donor and the acceptor substrates, wherein the association and dissociation rates of each regulate those of the other via conformational changes in the enzyme, altogether enhancing the binding affinity of both the substrates to drive the completion of catalysis. 14 Other studies have reported a negative cooperativity in substrate binding to the enzymes; however, no effect of the negative cooperativity was observed on the enzyme activity. 15 ITC-binding studies and NMR-based structural studies have been extremely useful to study the order of the binding of substrates; substrate-induced conformational change in the enzymes leads to allosteric communication between the substrates that directly affect the enzyme catalysis, 16,17 especially in the oligomeric enzymes, which have multiple catalytic sites on each monomer, and/or modular proteins or enzymes, which have catalytic sites on different domains, and these sites are separated by 10s of Å.…”
Section: Cooperativity and Thermodynamics Of Thementioning
confidence: 88%
“…Employing the sensitive methyl-reporters in macromolecular complexes using methyl-TROSY has become a versatile and generally accessible technique that is now broadly employed to characterise dynamics and allosteric regulation as well as key biological interactions [29][30][31][32][33][34].…”
Section: The Sensitive Reporters Of Large Macromolecular Complexesmentioning
confidence: 99%